ASSESSING THE EFFECTS OF TRAINING ON KNOWLEDGE AND SKILLS OF HEALTH PERSONNEL: A CASE STUDY FROM THE FAMILY HEALTH PROJECT IN SINDH, PAKISTAN - Hasnain, Syed Farid-ul-; Israr, Syed Muhammad; Jessani, Saleem (Journal of Ayub Medical College Abbottabad, 2005)
Background: The Family Health Project (FHP) was implemented in the province of Sindh during 1992-99 with the assistance of the World Bank. The project was designed to bring substantial changes in health care system for achieving improvement in the health status by strengthening the quality and integration of primary health care services. One of the major components of the project was to develop the institutional capacity of Ministry of Health in Sindh. This is a comparative analysis to assess the knowledge and skills of health care providers in Area Focus Approach (AFA) health facilities with the ones in non-AFA health care facilities. Methods: In order to obtain a representative sample, 8 districts were selected which included, Larkana, Khairpur, Nawabshah, Dadu, Tharparkar, Thatta, Karachi South, and Karachi West. A structured questionnaire was designed with various sections to assess the knowledge and skills of various cadres of health facility staff. Results: This comparative assessment has come up with some interesting results; there is a difference between the scores of knowledge and skills between AFA and non-AFA health care providers. This assessment identified some important methodological issues such as the use of base-line information for comparing the results and the selection of a comparable study population for controlling the confounding factors. Conclusions: These findings can be used as important lessons learned for producing better results of any post training assessment intervention. KEY WORDS: Family Health Project, Training, Knowledge, Skills